Analisis Tingkat Kebisingan di Depo Kayu Desa Tanjunganom, Kaliwiro, Wonosobo - Fajriyyah, Uyun Nafidzatul; Paramita, Dhea; Adi, Nugroho Prasetya (MASALIQ, 2023)
As humans who live on earth, it is undeniable that we live side by side with the surrounding environment such as land, water, air and sound. Threats or serious impacts on noise pollution, namely the decrease in the quality of the human environment because sound or noise pollution can disturb the environment. The purpose of this study was to determine the noise level in the Tanjunganom Village Wood Depot. This study uses a type of quantitative research by applying the NIOSH calculation method. The data collection techniques used included observation, interviews and documentation. Primary data was collected through field observations and interviews with the owners of the timber depot and documentation. In addition, secondary data was also collected from various references or written sources such as literature, journals, articles and books that are relevant to this research. The results of the study show that the noise intensity has not exceeded the threshold value which is set at > 85 dB. Thus, the noise at that location is still within the limits that are considered safe.